Activated mesenchymal stem cells increase drug susceptibility of methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa - Esfandiary, Reza; Saeedi, Pardis; Saffarian, Parvaneh; Halabian, Raheleh; Fooladi, Abbas Ali Imani (Folia microbiologica, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa are major causes of hospital-acquired infections and sepsis. Due to increasing antibiotic resistance, new treatments are needed. Mesenchymal stem cells (MSCs) have antimicrobial effects, which can be enhanced by preconditioning with antibiotics. This study investigated using antibiotics to strengthen MSCs against MRSA and P. aeruginosa. MSCs were preconditioned with linezolid, vancomycin, meropenem, or cephalosporin. Optimal antibiotic concentrations were determined by assessing MSC survival. Antimicrobial effects were measured by minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and antimicrobial peptide (AMP) gene expression. Optimal antibiotic concentrations for preconditioning MSCs without reducing viability were 1 μg/mL for linezolid, meropenem, and cephalosporin and 2 μg/mL for vancomycin. In MIC assays, MSCs preconditioned with linezolid, vancomycin, meropenem, or cephalosporin inhibited MRSA or P. aeruginosa growth at lower concentrations than non-preconditioned MSCs (p ≤ 0.001). In MBC assays, preconditioned MSCs showed enhanced bacterial clearance compared to non-preconditioned MSCs, especially when linezolid and vancomycin were used against MRSA (p ≤ 0.05). Preconditioned MSCs showed increased expression of genes encoding the antimicrobial peptide genes hepcidin and LL-37 compared to non-preconditioned MSCs. The highest hepcidin expression was seen with linezolid and vancomycin preconditioning (p ≤ 0.001). The highest LL-37 expression was with linezolid preconditioning (p ≤ 0.001). MSCs' preconditioning with linezolid, vancomycin, meropenem, or cephalosporin at optimal concentrations enhances their antimicrobial effects against MRSA and P. aeruginosa without compromising viability. This suggests preconditioned MSCs could be an effective adjuvant treatment for antibiotic-resistant infections. The mechanism may involve upregulation of AMP genes.
Keywords: Linezolid; Meropenem; Hepcidin; mezenchymální kmenové buňky; Antimicrobial Peptides; mikrobiální testy citlivosti; vankomycin; lidé; Anti-Bacterial Agents; antimikrobiální peptidy; Vancomycin; meropenem; methicilin rezistentní Staphylococcus aureus; cefalosporiny; Mesenchymal Stem Cells; Microbial Sensitivity Tests; stafylokokové infekce; hepcidiny; Cephalosporins; Mesenchymal stem cells; Hepcidins; Pseudomonas aeruginosa; linezolid; Staphylococcal Infections; Methicillin-resistant Staphylococcus aureus (MRSA); LL-37; antibakteriální látky; Methicillin-Resistant Staphylococcus aureus; Humans